Recycling of continental crust materials: Geochemical constraints from post-collisional alkaline intrusive rocks in the Dabie orogen - Sun, Guo-Chao; Xia, You-Shan; Wen, Gang; Qin, Lei; Xu, Qing-Yang; Dai, Li-Qun; Zhao, Zi-Fu (Frontiers in Earth Science, 2023)
Post-collisional alkaline intrusive rocks from the Dabie orogen were studied for their whole-rock major-trace elements and Sr-Nd-Hf-Pb isotopes, as well as zircon U-Pb ages and Hf-O isotopes. The results provide geochemical constraints on the nature of their mantle sources and thus insight into crust-mantle interaction in the continental collision zone. The alkaline intrusive rocks are composed of syenite and nepheline syenite. Syn-magmatic zircon U-Pb dating by LA-ICP-MS for them yielded Early Cretaceous ages of 131.3 ± 1.4 Ma to 122.6 ± 0.6 Ma, coeval with the post-collisional magmatism in the Dabie orogen. One relict zircon with U-Pb age of 211 Ma is consistent with the timing of metamorphism for the ultrahigh-pressure (UHP) metamorphic rocks in this orogen. They have arc-like trace element distribution patterns, such as enrichment in LILE (large ion lithophile element) and LREE (light rare earth element) but depletion in HFSE (high field strgenth element), and enriched whole-rock Sr-Nd-Hf isotope compositions with high (87Sr/86Sr)i ratios of 0.7077 to 0.7131 but negative εNd(t) values of -16.0 to -9.4 and εHf(t) values of -17.5 to -12.7. Their syn-magmatic zircons have three groups of Hf-O isotope compositions comparable to those of UHP metamorphic rocks in Central-South Dabie and North Dabie, which represent the upper and middle continental crust of the subducted South China Block, respectively. In this regard, slab–mantle interaction is evident during the continental collision. We suggest that the melts derived from the subducted South China Block reacted with the lithospheric mantle wedge of the North China Block, resulting in phlogopite-bearing metasomatites, whose partial melting would generate the post-collisional alkaline intrusive rocks during the Early Cretaceous.